2007
DOI: 10.1111/j.1440-0960.2007.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Solar keratosis: Epidemiology, pathogenesis, presentation and treatment

Abstract: Solar keratosis is a common problem encountered by dermatologists, particularly in Australia. Solar keratosis is most commonly found on sun-exposed areas such as the scalp, face and forearms. UV radiation is thought to be the major aetiological factor, with age, immunosuppression and human papillomavirus being important contributing factors. Solar keratosis usually presents as a discrete, variably erythematous and irregular lesion with a scaly surface. Although the exact rate of malignant transformation to squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 94 publications
1
45
1
3
Order By: Relevance
“…Although c‐PDT is a successful treatment for AK,5, 9, 24 the unpredictability of tolerance during treatment in some patients, extended treatment times, and costly instrumentation has limited its use. Daylight PDT is a simple and practical new treatment option for AK that allows large areas of actinic damage to be treated with reduced in‐clinic treatment times and little or no pain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although c‐PDT is a successful treatment for AK,5, 9, 24 the unpredictability of tolerance during treatment in some patients, extended treatment times, and costly instrumentation has limited its use. Daylight PDT is a simple and practical new treatment option for AK that allows large areas of actinic damage to be treated with reduced in‐clinic treatment times and little or no pain.…”
Section: Resultsmentioning
confidence: 99%
“…Using the Olsen three‐point scale,3 AK lesions are categorised as grade I (single or few lesions, better felt than seen), grade II (moderately thick lesions, easily felt and seen), or grade III (hyperkeratotic lesions). Significantly, AK have the potential to progress to invasive squamous cell carcinomas (SCC), however the actual risk of malignant transformation is poorly defined, with the reported risk varying from <0.025 to 16% per year 4, 5, 6. Because of the malignant potential and the unpredictability of the transformation from AK to SCC, consensus guidelines recommend that AK are removed using appropriate therapies to prevent progression to invasive disease 5, 7, 8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…embarrassment about scarring), and can negatively impact health-related quality of life. [34][35][36][37] In this study, ≥ 70% of patients reported improved cosmetic outcomes with IngMeb, with improved appearance and feel of the treated area.…”
Section: Discussionmentioning
confidence: 90%
“…Beyond these are further billions-around $1.2 billion in the United States [9•]-expended treating the related and highly prevalent skin lesions, actinic keratoses (AKs). AKs affect 5 % to 25 % of people in the United Kingdom and United States and up to 60 % in Australia [10,11], and are one of the strongest risk factors for skin cancer.…”
Section: Introductionmentioning
confidence: 99%